The degree to which Arabic language teachers in public and private sector schools employ the principles of Marzano’s dimensions of learning model in their teaching practices in the Sultanate of Oman from their point of view and from the point of view of educational supervisors (Damascus University Journal of educational and Psychologyical sciences, 2024)
The research aimed to reveal the degree to which Arabic language teachers employ the principles of Marzano's Dimensions of Learning Model in their teaching practices from their point of view and from the point of view of educational supervisors. And measuring the differences between the answers of the research sample members according to the two variables: (school affiliation, job description). The research relied on the descriptive analytical method, and the sample reached (174) Arabic language teachers, and (38) educational supervisors. The researcher applied to them a research questionnaire consisting of (50) items distributed over five dimensions, and the research concluded with the following results: The degree to which Arabic language teachers employed the principles of Marzano’s learning dimensions model in their teaching practices from their point of view was low with a rank average of (2.26). From the point of view of educational supervisors, the degree was very low, with an average rank of (1.75). There are differences according to the job description variable in favor of Arabic language teachers, and according to the school affiliation variable in favor of government schools in the Sultanate of Oman
Keywords: Degree; Employment; Arabic Language Teachers; Principles Of Marzano’s Learning Dimensions Model; Educational Supervisors.